Inflammatory myofibroblastic tumors of the pancreas in children: A case report and literature review. Issue 2 (January 2017) - Liu, Hsien-Kuan; Lin, Yung-Cheng; Yeh, Ming-Lun; Chen, Yaw-Sen; Su, Yu-Tsun; Tsai, Ching-Chung
Abstract: Introduction: Inflammatory myofibroblastic tumors are an uncommon neoplasm, which are very rarely located in the pancreas. Clinically and radiologically, this rare pancreatic tumor presents as an abdominal mass lesion that mimics other pancreatic tumors, and should therefore be considered in the differential diagnosis of pancreatic tumors. Clinical Findings and diagnosis: The 15-year-old boy complained of abdominal pain over the left upper quadrant with intermittent fever for 7 days. Abdominal sonography revealed one cystic lesion with a hyperechoic component in the left upper quadrant of the abdomen. Surgical excision was performed and postoperative findings indicated a pancreatic tail tumor. The pathology indicated inflammatory myofibroblastic tumors. To our knowledge, this patient is a unique case as the tumor was located in the pancreatic tail only, sparing the body. Interventions and outcomes: The patient underwent tumor resection and segmental resection of the transverse colon with simple closure. The patient had no evidence of disease recurrence at 3 years follow-up. Conclusion: Inflammatory myofibroblastic tumors of the pancreas in children are extremely rare. Surgical excision is the standard treatment, and corticosteroids use in children need more large-scale studies.